Assessing managers’ perception towards fitness: Examining a few procedures and steps / Saidin Wan Ismail and Norzaidi Mohd. Daud - Saidin Wan Ismail; Norzaidi Mohd. Daud (2017)
The founder of task-technology fit had proposed thirteen dimensions of fitness in evaluating the congruence between technology features and job specifications. The test conducted on managers in Islamic banking sector in Malaysia had shown that the components of fitness had reduced to more than half. The result of this study shows the different concept of fitness between two groups of technology users in United States of America (USA) and Malaysia.